The 1st International Electronic Conference on Genes: Theoretical and Applied Genomics 2020
DOI: 10.3390/iecge-07146
|View full text |Cite
|
Sign up to set email alerts
|

The Glyphosate Target Enzyme 5-Enolpyruvyl Shikimate 3-Phosphate Synthase (EPSPS) Contains Several EPSPS-Associated Domains in Fungi

Abstract: 5-enolpyruvylshikimate 3-phosphate synthase (EPSPS) is the central enzyme of the shikimate pathway to synthesize three aromatic amino acids in fungi, plants and prokaryotes. This enzyme is the target of the herbicide glyphosate. In most plants and prokaryotes, the EPSPS protein is constituted by a single domain, whereas in fungi, it contains several EPSPS-associated domains. Here, we perform a comprehensive analysis of 390 EPSPS proteins of fungi to determine the distribution and the evolution of the EPSPS-ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…A survey of bacteria in the human gut microbiome showed that around 30% of them were unclassified (i.e., EPSPS proteins from these species do not belong to any of the known classes), and additional studies are needed to identify other EPSPS classes. Also, it should be noticed that the EPSPS protein sequence in bacteria and plants is unidomain, whereas fungal EPSPS proteins contain several domains 59 . Thus, a protein folding in fungi may lead to a different response of the EPSPS enzyme to glyphosate.…”
Section: Discussionmentioning
confidence: 99%
“…A survey of bacteria in the human gut microbiome showed that around 30% of them were unclassified (i.e., EPSPS proteins from these species do not belong to any of the known classes), and additional studies are needed to identify other EPSPS classes. Also, it should be noticed that the EPSPS protein sequence in bacteria and plants is unidomain, whereas fungal EPSPS proteins contain several domains 59 . Thus, a protein folding in fungi may lead to a different response of the EPSPS enzyme to glyphosate.…”
Section: Discussionmentioning
confidence: 99%
“… Domains: domain names; Freq: frequency of the domain in the subset of proteins with more than one domain; Sp: number of species in the pfam database (on May 2022) with at least one copy of the domain; D: number of domain architectures in pfam database (on May 2022); and Function: description of the product. This table has been modified with permission by authors from [ 26 ]. …”
Section: Figurementioning
confidence: 99%
“…Glyphosate (Monsanto, Belgium) is the world's most widely used non-selective systemic 1 herbicide used to control weeds or suppress cover crops (Woodburn 2000;Duke 2021). It kills plants by inhibiting the 5-enolpyruvylshikimate-3-phosphate synthase (EPSP synthase), a key enzyme in the shikimate biosynthetic pathway (Tzin et al 2012;Helander et al 2012;Tall and Puigbò 2020). Over 30% of the C fixed by the plants passes through this pathway (Shaner 2006;Tzin et al 2012).…”
Section: Introductionmentioning
confidence: 99%